Sámi reindeer herders’ perspective on herbivory of subarctic mountain birch forests by geometrid moths and reindeer: a case study from northernmost Finland - Vuojala-Magga, Terhi (Springerplus, 2015)
INTRODUCTION: Geometrid moths and semi-domesticated reindeer are both herbivores which feed on birch leaves in the subarctic mountain birch forests in northern Fennoscandia. The caterpillars of autumnal and winter moths have episodic outbreaks, which can occasionally lead to extensive defoliation of birch forests. Earlier studies have shown that reindeer have a negative effect on the regeneration of defoliated birches by grazing and browsing their seedlings and sprouts. CASE DESCRIPTION: We interviewed 15 reindeer herders in the Kaldoaivi and Paistunturi herding co-operative in northernmost Finland in order to analyse their past, present and future views on the behaviour of moths and the growth of mountain birches. We investigate the behaviour of the two herbivores by combining the indigenous knowledge (IK) of Sámi herders with the results of relevant studies in biology and anthropology, applying niche construction theory (NCT) in doing so. DISCUSSION AND EVALUATION: In the first stage, the niche constructors (moths, reindeer, herders, mountain birch and other organisms) are looked upon as “equal constructors” of a shared niche. As changes unfold in their niche, their role changes from that of constructor to key constructor. The role and importance of niche constructors were different when nomadic pasture rotation was used than they are today under the herding co-operative system. Niche construction faced its most radical and permanent negative changes during the border closures that took place over the latter half of the 19(th) century. The large-scale nomadic life among the Sámi herders, who migrated between Finland and Norway, came to an end. This phase was followed by stationary herding, which diminished the possibilities of reindeer to look for various environmental affordances. Difficult snow conditions or birch defoliation caused by moth outbreaks made the situation worse than before. Eventually reindeer became key constructors, together with moth larvae, leading to negative ecological inheritance that forced herders to use new, adaptive herding practices. CONCLUSIONS: Both the scientific data and the IK of herders highlight the roles of reindeer and herders as continuous key constructors of the focal niche, one which stands to be modified in more heterogenic ways than earlier due to global warming and hence will result in new ecological inheritance.